Impact of Job Satisfaction on Job Performance of Nurses at Al-SuwairaGeneral Hospital - okab, ammar (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To measure the level of job satisfaction and job performance of nurses and to find outthe association between participants' socio-demographic characteristic of nurse and their jobsatisfaction and job performance.Methodology: A descriptive analytic study design was carried out to measure the nurses' level of jobsatisfaction and job performance in Al-Suwaira general hospital and to find out the association betweennurses and their socio-demographic characteristic. The study was started from March 5th, 2017 toSeptember 31th, 2017. The sample was Non - probability (purposive) sample of (100) nurses wereselected according to the study that are actual working in nursing department in Al-Suwaira GeneralHospital. The data were collected by direct interview using specific questionnaire thats composed ofthree parts (27) items which are: Part (1) Socio-demographic characteristics which included sevenitems (age, gender, marital status, level of education, participation in training courses or scientificconferences inside or outside Iraq and engaged in the nursing by your choice). Part (2) which dealswith job satisfaction and includes (10) items and Part (3) which deals with job performance including(10) items. Data were analyzed by using (SPSS) package version 20. Descriptive data throughdetermination of: Frequency, percentage and mean of score. Inferential statistical data analysisapproach: used by enforcement of the Chi –square test used for determining the association betweenSocio-demographic characteristics and job satisfaction, job performance, testing the significant of thecontingency coefficient. For this study the significant P-value ≤ 0.05.Results: ( (77%) were female, (56%) were married, the total grade level of job satisfaction is low, andpresent highly statistical significant association between items which is related to job satisfaction andgender and highly statistical significant association between the items related to the job performanceand age.Recommendations: The study recommends that establish and follow up programs about jobsatisfaction to increase job performance